Diversity of polyporales and the application of Ganoderma Australe (fr.) pat. in biopulping of empty fruit bunches of Elaeis Guineensis / Mohamad Hasnul Bolhassan - Mohamad Hasnul, Bolhassan (2013)

(untitled)
Diversity and distribution of Polyporales in Malaysia was investigated by collecting basidiocarps from trunks, branches, exposed roots and soil from six states (Johore, Kedah, Kelantan, Negeri Sembilan, Pahang and Selangor) in Peninsular Malaysia and Federal Territory Kuala Lumpur. The morphological study of 99 basidiomata collected from 2006 till 2007 and 241 herbarium specimens collected from 2003 - 2005 were undertaken. Sixty species belonging to five families: Fomitopsidaceae, Ganodermataceae, Meruliaceae, Meripilaceae and Polyporaceae were recorded. Polyporaceae was the dominant family with 46 species identified. The common species encountered based on the number of basidiocarps collected were Ganoderma australe followed by Lentinus squarrosulus, Earliella scabrosa, Pycnoporus sanguineus, Lentinus connatus, Microporus xanthopus, Trametes menziesii, Lenzites elegans, Lentinus sajor-caju and Microporus affinis. Eighteen genera with only one specie were also recorded i.e. Daedalea, Amauroderma, Flavodon, Earliella, Echinochaetae, Favolus, Flabellophora, Fomitella, Funalia, Hexagonia, Lignosus, Macrohyporia, Microporellus, Nigroporus, Panus, Perenniporia, Pseudofavolus and Pyrofomes. This study shows that strains of the G. lucidum and G. australe can be identified by 650 base pair nucleic acid sequence characters from ITS1, 5.8S rDNA and ITS2 region on the ribosomal DNA. The phylogenetic analysis used maximum-parsimony as the optimality criterion and heuristic searches used 100 replicates of random addition sequences with tree-bisection-reconnection (TBR) branch-swaping. ITS phylogeny confirms that G. lucidum and G. australe were named correctly based on the molecular analysis even though the strains exhibited differences in morphological characteristics. Thirty-seven selected cultures of Polyporales were qualitatively assayed for the production of amylases, cellulases, laccases and lignin peroxidases after three to seven days incubation at 25±2°C. Two strains - Ganoderma australe KUM60848 and Favolus iii tenuiculus KUM60803 demonstrated good enzymes production and were selected to undergo solid substrate fermentation of oil palm empty fruit bunches (EFB). The study was conducted to analyse the enzymatic activity (U/ml) of cellulase, amylase, laccase, lignin peroxidase, xylanase and β-D-glucosidase. Ganoderma australe showed the highest enzymes activity on the 14 and 21 days of incubation compared to F. tenuiculus and was selected as potential candidate for biopulping of oil palm (Elaeis guineensis) empty fruit bunches. The property of pulp produced by oil palm empty fruit bunches through solid substrate fermentation with G. australe KUM60848 were then analysed at 14 and 21 days of incubation. The empty fruit bunches was pulped by applying soda pulping process. The result showed that the pulping process influenced the pulping properties. Pre-treatment by G. australe for 14 days produced the lowest degree of material dissolved while pre-treatment at 21 days had the highest degree of material dissolved as indicated by the pulp yields. Compared to control, the biopulping yield using G. australe had increased to a maximum of 18%. The pulping process also influenced the paper properties i.e. all zero-span tensile indices of pulp were lower than control (conventional pulping), while the fibre strength decreased by 11% and 6% at day 14 and 21 respectively. In conclusion, the 14 days of solid substrate fermentation by G. australe performs better pulp and paper properties than 21 days in biopulping of EFB.